Implementation of the E-Pocket Book to Improve Learning Outcomes in Economics at Madrasah Aliyah Madinatussalam, Bandar Khalifah Regency, Indonesia - Nur Afrianti; Dede Ruslan; Muhammad Yusuf (BIRCU, 2021)
Teaching materials playing a vital role in supporting the learning process in a classroom. The right teaching materials will make the learning process more effective. The problem that is often faced by students is the teaching materials that are not appropriate, so that it lowers student learning outcomes. This causes the low learning outcomes of students in class XI economics MA Madinatusallam. For this reason, researchers try to investigate the effectiveness of e-pocketbook teaching materials. Field test results showed that the experimental class obtained higher learning outcomes than the control class, with a significant difference (p = <.05).